2017
DOI: 10.1186/s13046-017-0593-2
|View full text |Cite
|
Sign up to set email alerts
|

PDL1 And LDHA act as ceRNAs in triple negative breast cancer by regulating miR-34a

Abstract: BackgroudThe purpose of this study was to elucidate the regulation of programmed death ligand 1 (PDL1), lactate dehydrogenase A (LDHA) and miR-34a in triple negative breast cancer (TNBC) and to explore the function and mechanism of PDL1 and LDHA as competitive endogenous RNAs (ceRNAs) in TNBC via regulation of miR-34a.MethodsWestern blotting, quantitative RT-PCR (qRT-PCR) and immunohistochemistry (IHC) assays were conducted to explore the expression of PDL1, LDHA and miR-34a in TNBC and correlations between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 38 publications
1
34
0
1
Order By: Relevance
“…Accumulating evidence has demonstrated that aberrant expression of miR-34a regulates the progression of various neoplasms (25), including glioma (26), breast cancer (27,28), cervical cancer (29), cholangiocarcinoma (30) and multiple myeloma (31). The results of the present study demonstrated that the expression level of miR-34a was reduced in RB tissues compared with that in paracarcinoma tissues (P<0.05).…”
Section: Discussionsupporting
confidence: 50%
“…Accumulating evidence has demonstrated that aberrant expression of miR-34a regulates the progression of various neoplasms (25), including glioma (26), breast cancer (27,28), cervical cancer (29), cholangiocarcinoma (30) and multiple myeloma (31). The results of the present study demonstrated that the expression level of miR-34a was reduced in RB tissues compared with that in paracarcinoma tissues (P<0.05).…”
Section: Discussionsupporting
confidence: 50%
“…20 with poor survival, such as breast cancer, 28 colorectal cancer, 29 pancreatic cancer. 20 with poor survival, such as breast cancer, 28 colorectal cancer, 29 pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…LDHA, as one of the key metabolic enzyme, is essential for the conversion of pyruvate into lactate, and might be involved in tumor initiation and metabolism by regulating warburg effect. Increased LDHA has been observed in variety of tumors and is correlated with poor survival, such as breast cancer, 28 colorectal cancer, 29 pancreatic cancer. 30 Additionally, several studies have found that LDHA silencing could reduce tumor occurrence and growth, suppress metastasis and increase apoptosis in many cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The term microRNA (miRNA) signatures has attracted increased attention in recent years, which could potentially be used as predictive or prognostic biomarkers . The combined analysis of a panel of biomarkers, rather than individual analyses, as a nomogram is the most promising approach that is powerful enough to change clinical management .…”
mentioning
confidence: 99%
“…The term microRNA (miRNA) signatures has attracted increased attention in recent years, which could potentially be used as predictive or prognostic biomarkers. [8][9][10][11][12][13] The combined analysis of a panel of biomarkers, rather than individual analyses, as a nomogram is the most promising approach that is powerful enough to change clinical management. 7,[14][15][16] Although classifier models based on clinical-associated factors, such as axillary ultrasound (AUS) and tumor size, have been investigated and demonstrated to be useful for ALN metastasis prediction in patients with BC, an optimal approach that combines multiple miRNAs biomarkers as a predictive signature has yet to be developed.…”
mentioning
confidence: 99%